THE URGENCY OF MILITARY JUDICIAL REFORM UNDER THE PRINCIPLE OF NEMO EST SUPRA LEGES: A CASE STUDY ON THE SHOOTING OF RENTAL BUSINESS OWNER - Islami, Diajeng Dhea Aura; Lewoleba, Kayus Kayowuan (Pena Cendekia Insani, 2025)
This study examined the urgency of reforming Indonesia’s military justice system in accordance with the principle of Nemo Est Supra Leges, which asserts that no individual stands above the law. The research aimed to analyze the normative disharmony between Article 9 of Law No. 31 of 1997 on Military Courts and Article 65 of Law No. 34 of 2004 on the Indonesian National Armed Forces, as well as to evaluate the application of the Nemo Est Supra Leges principle in the case involving the shooting of a car rental business owner by members of the Indonesian Navy. The study employed a normative juridical method with statutory, case, and conceptual approaches. The findings revealed that the inconsistency between the two legal provisions resulted in overlapping jurisdictions and weakened the principle of equality before the law within the national judicial system. Moreover, the implementation of the Nemo Est Supra Leges principle had not been fully realized. The study concluded that reforming the military justice system is imperative to ensure fair, transparent, and accountable law enforcement in alignment with the rule of law in a democratic state.